2009
DOI: 10.4103/0970-938x.54832
|View full text |Cite
|
Sign up to set email alerts
|

Anterograde synaptic transport of neuronal tracer enzyme (WGA-HRP): further studies with Rab3A-siRNA in rats

Abstract: Neuronal tracer enzyme of wheat germ agglutinin conjugated horseradish peroxidase (WGA-HRP) was employed to elucidate the detailed morphology of anterograde synaptic transport. After injection of WGA-HRP into the vagus nerve, sensory terminals in the nucleus of solitary tract (NST) were observed at the electron microscopic level using the tetramethyl benzidine and diaminobenzidine methods. In neuropil of the NST, electron-dense HRP-reaction product (HRP-RP) showed various types of lysosomallike structures. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 149 publications
0
3
0
Order By: Relevance
“…Furthermore, it was of particular interest that the neuronal transcytosis of tracer enzyme appeared to have occurred randomly at various portions of the axodendritic membranes. The appearance of the HRP-RP in relation to the membranes was characterized as either the "passing type" (Figure 3(a)) or, because of the indentation of axodendritic membranes into the dendrites, as the "secretion type" (Figures 3(b)-(d)) [9]. = 0.1 μm in (a,b,e), 0.2 μm in (c,d) and 1.0 μm in (f).…”
Section: Light and Electron Microscopical Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was of particular interest that the neuronal transcytosis of tracer enzyme appeared to have occurred randomly at various portions of the axodendritic membranes. The appearance of the HRP-RP in relation to the membranes was characterized as either the "passing type" (Figure 3(a)) or, because of the indentation of axodendritic membranes into the dendrites, as the "secretion type" (Figures 3(b)-(d)) [9]. = 0.1 μm in (a,b,e), 0.2 μm in (c,d) and 1.0 μm in (f).…”
Section: Light and Electron Microscopical Observationsmentioning
confidence: 99%
“…In a recent study using Rab3A gene-deleted mice, synaptic vesicle docking to the presynaptic membrane and regulation of synaptic vesicle exocytosis were shown to be impaired at the neuromuscular synapses [7,8]. Furthermore, our previous study in-dicated that Rab3A-siRNA injected into the rat vagus nerve is involved in modulating the level of transcytosis of the tracer enzyme, wheat germ agglutinin conjugated with horseradish peroxidase (WGA-HRP), at synaptic junctions [9]. However, the mechanisms involved in this effect of Rab3A-siRNA on transcytosis remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested its mechanism to be "diacrine secretion" which was characterized by passing through cell membrane. With respect to the non-vesicular transport, our recent studies in Rab3A-siRNA-and ethanol-treated rats also indicated alteration of membrane of the vagus nerve terminals in the nucleus of solitary tract and it was called "apocrine-like structure" which was quite different from normal vesicular exocytosis (5)(6)(7). On the basis of its morphological characteristic, it was hypothesized that this structure possibly plays an important role in the process of synaptic transport of materials including proteins.…”
Section: Introductionmentioning
confidence: 99%